Non-CF Bronchiectasis as a Possible Indicator of a Primary Immunodeficiency: Diagnosis, Clinical Course, and Quality of Life in a Pediatric Cohort - Klemann, Christian; Kellermann, Kinga Beata; Ehl, Stephan; Stenzel, Martin; Mueller, Christoph; Heinzmann, Andrea; Bode, Sebastian Felix Nepomuk (Klinische Pädiatrie, 2019)
Background Non cystic fibrosis bronchiectasis (NCBE) is an increasingly recognized chronic, progressive respiratory disorder with significant morbidity also in children and adolescents.Methods We longitudinally assessed a cohort of 35 pediatric patients with NCBE and investigated underlying diagnosis, symptoms, clinical course, treatment, and quality of life.Results NCBE were diagnosed at a mean age of 9.5 (±5.3) years. In half of the children NCBE were found prior to identification of the causative diagnosis. Primary immunodeficiency (PID) was identified as the underlying diagnosis in 24/35 (68%) cases, of which two-thirds showed antibody deficiency. In the 11 non-PID cases ciliopathies were most common (n=7). Clinical aspects such as manifestation age, cough or dyspnea symptoms, and exacerbation frequency did not differ significantly between PID and non-PID patients. Likewise, quality of life (QoL) was equally reduced in both groups. Lung function test parameters were stable under appropriate therapy in all children. The majority in both groups was insufficiently vaccinated against influenza and pneumococci.Conclusion Our data indicates that NCBE need to be especially appreciated as a presenting sign of PID in pediatric patients. Thus, occurrence of NCBE should warrant rigorous diagnostics to identify the underlying condition. In our cohort NCBE themselves rather than the causative diagnoses seem to dictate the clinical course of disease and reduce QoL in children. More intensive efforts have to be undertaken to vaccinate patients according to recommendations.
Keywords: bronchiectasis; non-CF; immunodeficiency; quality of life